2008
DOI: 10.1590/s0034-72992008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Deficiência auditiva na toxoplasmose congênita detectada pela triagem neonatal

Abstract: Congeni tal toxoplasmosis may cause sensorineural deficit in up to 20% of the patients and proper treatment in the first year improves prognosis. In Brazil, this infection's impact on hearing impairment is unknown. Aim: To evaluate hearing of newborns with congenital toxoplasmosis identified by the newborn screening service. Method: This prospective study analyzed children with congenital toxoplasmosis identified by newborn screening (IgM anti-T.gondii) in Belo Horizonte during 2003/2004. The presence of IgM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(41 reference statements)
1
15
0
3
Order By: Relevance
“…The occurrence of retrocochlear auditory disorders in 20.8% of the SG children in the present study is similar to that found in the literature, between 21.1 and 35.5% 4,11,25 . However, it differed from other studies in which the prevalence found was significantly lower or even zero 14,23,26,27 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The occurrence of retrocochlear auditory disorders in 20.8% of the SG children in the present study is similar to that found in the literature, between 21.1 and 35.5% 4,11,25 . However, it differed from other studies in which the prevalence found was significantly lower or even zero 14,23,26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies have found a prevalence of congenital toxoplasmosis between 0.6-1.3/1000 live births in different regions of Brazil [4][5][6] . It has been suggested that the chance of transmission of toxoplasmosis from mother to fetus ranges from 18.5 to 23% 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactating infants according to values (mean, standard deviation and median in milliseconds -ms) and a comparison of absolute wave I, III and V and interpeaks I-III, III-V and I-V latencies at 80 dBHL, and the absolute wave V latency at 60, 40 Table 4 shows the wave I, III and V absolute and interpeak latencies at 80 dBHL and wave V latency at 60, 40 and 20 dBHL in term and premature infants, and the comparison between groups. Statistically significant differences were found in a comparison of absolute latencies for waves I, III and V at 80 dB between term and premature infants; higher values were found in premature infants at all intensities compared to term infants.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with this disease were referred for audiological investigation, the results of which showed that 21.1% of these infants had sensorineural hearing loss and 10.5% had conduction hearing loss. 22 Hearing loss in CMV infection is generally progressive. The infant with CMV infection in this study acquired the disease after a blood transfusion; statistical significance, however, was not attained.…”
Section: Discussionmentioning
confidence: 99%